A DETECT PARTIAL DISCHARGE IN ISOLATOR USING A FLUKE ii910 SONIC INDUSTRIAL IMAGER IN PTR 03 FEEDER (SARIBU DOLOK) - Akbar Primary S; Hamdani Hamdani; Siti Anisah (Sean Institute, 2022)
Partial discharge is a very serious problem that should be monitored quickly. The cause of Partial discharge failure is due to the presence of voids filled with gas/air in the insulation material. Partial discharge can also be regarded as losses because it can reduce the quality of the insulation material. This study aims to detect partial discharge using the Fluke ii910 Sonic Industrial Imager. Tests in this study using descriptive quantitative research methods. From the tests that have been carried out, it can be concluded that using the Fluke ii910 Sonic Industrial Imager can make it easier to find partial discharges on the insulator and minimize the impact of interference caused by partial discharges